FAIRshake: Toolkit to evaluate the FAIRness of research digital resources - Clarke, DJB; Wang, L; Jones, A; Wojciechowicz, ML; Torre, D; Jagodnik, KM; Jenkins, SL; McQuilton, P; Flamholz, Z; Silverstein, MC; Schilder, BM; Robasky, K; et al. (Cell Press, 2019)
As more digital resources are produced by the research community, it is becoming increasingly important to harmonize and organize them for synergistic utilization. The findable, accessible, interoperable, and reusable (FAIR) guiding principles have prompted many stakeholders to consider strategies for tackling this challenge. The FAIRshake toolkit was developed to enable the establishment of community-driven FAIR metrics and rubrics paired with manual and automated FAIR assessments. FAIR assessments are visualized as an insignia that can be embedded within digital-resources-hosting websites. Using FAIRshake, a variety of biomedical digital resources were manually and automatically evaluated for their level of FAIRness.